2020
DOI: 10.1002/ieam.4349
|View full text |Cite
|
Sign up to set email alerts
|

Human Activities Impact Prediction in Vegetation Diversity of Lar National Park in Iran Using Artificial Neural Network Model

Abstract: The effects of livestock and tourism on vegetation include loss of biodiversity and in some cases species extinction. To evaluate these stressor-effect relationships and provide a tool for managing them in Iran's Lar National Park, we developed a multilayer perceptron (MLP) artificial neural network model to predict vegetation diversity related to human activities. Recreation and restricted zones were selected as sampling areas with maximum and minimum human impacts. Vegetation diversity was measured as the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Artificial neural networks (ANNs) are mathematical models that can be used for complex and non-linear processes 16 , 17 . ANNs can simulate the behavior of the human brain 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial neural networks (ANNs) are mathematical models that can be used for complex and non-linear processes 16 , 17 . ANNs can simulate the behavior of the human brain 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing levels of NO 2 pollution in many countries, especially in metropolises such as Tehran. Therefore forecast, controlling and counteracting NO 2 is a vital issue in urban management 4 .Artificial neural networks (ANNs) are mathematical models that can be used for complex and non-linear processes 16,17 . ANNs can simulate the behavior of the human brain 18,19 .…”
mentioning
confidence: 99%
“…In a published study authors observed the signi cant impact of different altitudes and phenological stages on the essential oil yield [22,23]. It was revealed that plant performance is strongly in uenced by various factors such as altitude, climate, soil, developmental stages, extraction and analysis methods, genetic factors, abiotic stresses, and slope and modeling techniques can predict these factors in other areas [24,25,26,27,28]. The results of the current study were compatible with other studies that found the highest content of essential oil of Origanum majorana in the vegetative stage, so they proposed the vegetative stage as the best stage to harvest Origanum majorana [29,30,31,32,33,34,35,36].Similar results were also found byon the essential oil content of Nepeta kotschyr [37].…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that plant performance is strongly influenced by various factors such as altitude, climate, soil, developmental stages, extraction and analysis methods, genetic factors, abiotic stresses, and slope. Modeling techniques were used to predict these factors (Jahani Goshtasb et al, 2020;Jahani & Rayegani, 2020;, 2021Saffariha et al, 2020). Because climate is directly related to changes in altitude, when we considered altitude, climate, and temperature have been examined then.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, ANNs are capable of learning from real samples of a problem using transfer functions between neurons and specific algorithms without any prior knowledge. 16,17 ANNs have been proposed as a reasoning method due to high-performance characteristics and flexibility in modeling complex relationships than the traditional statistical methods used for the extraction of prediction equations in clinical decision making. This is due to the fact that altering the number of layers and hidden units, applying different algorithms, changing the training cycles or modifying the weight trying to find the best solution is easy in a neural network.…”
mentioning
confidence: 99%